THE "GOLDEN SPIKE" METHOD: A PROBLEM OF GEOLOGICAL AND PHYSICAL TIME COMPATIBILITY - Lazarev S.S. (My University, 2003)
The "golden spike" is a geological time mark at the axis of physical time. such an interpretation is admissible only for particular sections, because the boundaries (line)in the physical and geological time scales differ in essence from each other. In the physical time scale, they are virtual, inaccessible for direct observations, while the geological boundaries are real and classifiable by essence. Strategically, the GSSP (Global Stratotype Section and Point) method means a replacement of geological time (the succession of historical-geological processes) by the physical time standards in the International stratigraphic scale (ISS).